2021
DOI: 10.1007/s42979-021-00733-2
|View full text |Cite
|
Sign up to set email alerts
|

Computer Science Students’ Perceptions of Emergency Remote Teaching: An Experience Report

Abstract: In the first 6 months of 2020, the COVID-19 pandemic forced numerous universities across the globe to quickly transfer all their courses online, a response known as Emergency Remote Teaching. Courses initially designed for face to face delivery had to be quickly adapted to a new online format. In this paper, we study the perception of the transition to remote teaching in a group of computer science students. Despite the advantage given by an average higher computer literacy, the results of this study suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
15
2
1
Order By: Relevance
“…During the COVID-19 pandemic, several research studies were conducted and continues to be conducted around the impact of COVID-19 on society [6,7,18,19]. To the best of our knowledge, comparative research on countries with such vastly different economic and social backgrounds is limited.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, several research studies were conducted and continues to be conducted around the impact of COVID-19 on society [6,7,18,19]. To the best of our knowledge, comparative research on countries with such vastly different economic and social backgrounds is limited.…”
Section: Figurementioning
confidence: 99%
“…In South Africa, the first lockdown measures also came into effect on the 26 March 2020, and Hungary commenced lockdown on the 28 March 2020. Virtual learning replaced face-to-face delivery at all educational levels [6]. Usually, such a switch to virtual delivery would be instituted with a great deal of preparation and after a period of reflection [7].…”
Section: Introductionmentioning
confidence: 99%
“…Student Motivation: Toti & Alipour (2021) explain that students who have experience being on a college campus develop more self-motivation over students deficient in the same experience. Especially during the pandemic, the study found that students who learned remotely had a challenging time learning due to the independent nature of remote courses requiring higher levels of self-driven motivation.…”
Section: Discussionmentioning
confidence: 99%
“…A modo de reflexión, la enseñanza aprendizaje en pandemia tuvo un impacto bien alto en la transición de estudiantes de cursos de nivel inferior (Toti y Alipour, 2021). Por una parte, citando a Li et al (2021) esta transición fue debido a la ausencia de clases experimentales/ prácticas, así como la incertidumbre de la apertura de la universidad.…”
Section: Cont Cuadrounclassified